Government Sponsored Health Insurance Coverage and Out-of-Pocket Spending Among Elderly in Kerala: A Cross-Sectional Study - Philip NE; Ravindran TKS (Journal of Aging Research And Healthcare, 2017)
We aimed to find the population coverage, health service utilization and out-of-pocket spending among the elderly who are insured under Comprehensive Health Insurance Scheme (CHIS), Kerala through a longitudinal study of 600 non-rich households for nine months. The study found that only 57.7% the elderly were insured under CHIS which is lower than the population average of 80%. Single elderly from a socially backward caste, living alone in kutcha or semi-pucca houses were excluded from CHIS. Even though insured elderly had more episodes of hospitalization, only 38.4% of the elderly could make use of CHIS smart card for payment during hospitalization and 43.6% of the episodes were covered by CHIS. The mean indirect out-of-pocket expenses among insured elderly who had used smart cards for hospitalization (INR 7679.25) was higher than that for the un-insured (INR 4455.26), p = 0.027. The mean monthly drug expenditure (INR 1105.09) was also significantly higher among the insured as compared to the un-insured elderly (INR 650.03), p=.004. More than 80% of the hospitalized households had to use distress finance mechanisms to meet health- related expenses. We found that population coverage among elderly did not translate into service coverage and thus financial risk protection was not achieved even in a state like Kerala which is considered to be well-performing in terms of health insurance coverage. This study points out that elderly being a vulnerable group with special needs require a more comprehensive service package including chronic disease care, and a higher level of financial coverage.
Keywords: Elderly